Recent progress and technical challenges in using calcium sulfoaluminate (CSA) cement. (March 2023) - Tao, Yaxin; Rahul, A.V.; Mohan, Manu K.; De Schutter, Geert; Van Tittelboom, Kim
Abstract: Calcium sulfoaluminate (CSA) cement can be used as a replacement for Portland cement to reduce CO2 emissions. However, the performance of CSA cement remains unknown with regard to its hydration mechanism, mechanical and long-term performance. Therefore, it would be beneficial to consolidate the literature on CSA cement to facilitate its use in the construction industry. To this end, recent progress and technical challenges of using CSA cement are discussed in this paper. We begin with the introduction of the different types of CSA cement and the manufacturing process. This is followed by a detailed discussion on the hydration mechanisms and phase assemblage, mechanical performance, and long-term durability of CSA cement. Finally, the applications of CSA cement are discussed.